SURAT YAKOBUS KEPADA MUSYAWARAH PARIPURNA IAMS DI SEOUL - Elsa Temez (Institut Filsafat dan Teknologi Kreatif Ledalero, 2016)
In his classic study of mission, David Bosch (1991) outlined three biblical paradigms of mission from Matthew, Luke and Paul. In this essay, the author proposes a further paradigm drawn from the Letter of James. James is viewed as a circular written for Jewish-Christian migrant communities to encourage them towards a mission ad intra and intra gentes. James makes six calls to radical conversion: he strenghtens the readers’ hope as they struggle against overwhelming odds, he then calls for conversion against greed and against ambition and power struggles, exhorting them not to be seduced by the values of society, and so leave behind their friendship with the world; he finally calls for faithcoherence. The essay concludes with four applications of the “James Paradigm” for the renewal of mission witness among Christians today. Keywords: Epistle of James, the paradigm of an internal mission,repentance, characterististics of James’ mission, consistent faith ———————————————————————————————————————— Surat Yakobus kepada Musyawarah Paripurna IAMS di Seoul. David J.Bosch, dalam buku klasiknya Transformasi Misi Kristen, menganalisis tiga sumber Alkitab dalam Perjanjian Baru (Matius, Lukas, dan Paulus) guna merumuskan tiga paradigma misioner yang berasal dari ketiganya. Di dalam esai ini penulis menampilkan paradigma Surat Yakobus. Yakobus menyajikan segi-segi yang tidak tampak dalam ketiga paradigma di atas, yang dianggap relevan dengan situasi kita saat ini. Artikel menyimpulkan empat aplikasi pandangan Yakobus dalam rangka pembaruan kesaksian misi Kristen dewasa ini. Kata-kata kunci: Surat Rasul Yakobus, paradigma misi internal,pertobatan, ciri-ciri misi Yakobus, iman konsisten